The Effect of Digital Literacy on the Risks of Children Dropping Out of School During the Covid-19 Pandemic - Afif Muzayyin; Dwini Handayani (JTP - Jurnal Teknologi Pendidikan, 2023)
The Covid-19 pandemic has negative implications for all aspects of life, including aspects of education. It is feared that the transition to a distance learning system (PJJ) that adopts digital technology will reduce students' learning abilities  (learning loss) and potentially increase the risk of dropping out of school. This study aims to study the effect of digital literacy on the risk of dropping out of school for children aged 7-18 years during the Covid-19 pandemic. This study used a quantitative approach that using secondary data of Susenas 2021, Podes 2021, and IP-TIK 2021 publications with 250,921 samples of unit analysis being individuals aged 7-18 years with school status in the academic year (2019/2020) at the elementary to high school levels. Data analysis was performed using descriptive methods and multilevel binary logistic regression. The results of the analysis show that digital literacy as a proxy for digital access (use of mobile phones, computers/laptops, and internet access) has a negative significant effect on the risk of dropping out children of school. Childrens that have higher the digital literacy will have the lower the risk of dropping out children of school. The significant control variables were sex, school level, employment status of the head of household, length of schooling of the head of household, household expenditure quintile, and classification of residence. While the contextual (regional) variable that has a significant effect on the risk of dropping out of school is the information and communication technology development index (IP-TIK)